Terrorism and counterterrorism today - Deflem, Mathieu (Bingley, U.K. : Emerald, 2015)
This volume contains chapters dealing with a variety of issues related to terrorism and counterterrorism and the study thereof, especially in relation to crime, criminal justice, law, and social control. The book gathers chapters involving a variety of issues and multiple theoretical approaches and methodological orientations. The topics include, amongst others, lone-wolf terrorism, the policing of terrorism, radicalization, suicide terrorism, torture, and counterterrorism policies. The themes of the book remain timely some 15 years after the events of September 11 2001 as evinced from the manifold continuing terrorism-related issues around the world today. This collection will be useful to students and scholars in sociology, criminology, law, political science, and public policy.
Terrorism as gravitational attraction / Mark Cooney, Nicole Bigman -- How has criminology contributed to the study of terrorism since 9/11? / Gary Lafree, Laura Dugan -- Terrorism and genocide / Bradley Campbell -- The emergence of lone wolf terrorism: patterns of behavior and implications for intervention / Brent L. Smith, Jeff Gruenewald, Paxton Roberts, Kelly R. Damphousse -- Terrok: a hybrid perpetrator in individualized terrorism warfare / Thomas Kron, Andreas Braun, Eva-Maria Heinke -- Second order terrorism / Willem De Lint -- Prosecuting terrorism: challenges in the post-9/11 world / Christopher A. Shields, Brent L. Smith, Kelly R. Damphousse -- The social construction of terrorism / Cynthia A. Karaffa -- Suicide attacks and the social structure of sacrifice / Jason Manning -- Changes in local law enforcement brought about by 9/11 / Gregg W. Etter Sr. -- State legitimacy and terrorism: implications for counterterrorism policy / Jennifer C. Gibbs -- Postmodern torture and the conceits of the war on terror / Michael Welch.
Includes bibliographical references.
Print version record
Keywords: Social Science -- Criminology; Crime & criminology; Terrorism, armed struggle; Terrorism; Terrorism -- Prevention